(NkWANTOWOHIMI^ESKAQ I STATISTI^ESKAQ TEORIQ RASTWOROW (B:s (NwY^ISLITELXNYE METODY I IH PRIMENENIE (B/s - (NsIMKIN(B, (NbORIS qKOWLEWI^s; (N{EJHET(B, (NiGORX iLXI^s ((NmOSKWA (B:s (NhIMIQ(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 240-252 (489 (NNAZW(B.)s
Keywords: (NmATEMATI^ESKIE METODYs; (NrASTWORY(B, (NTEORIQs